Effect of Project Methods on Early Children's Environmental Care Behavior - Yuli Surohmah; Lilis Madyawati; Febru Puji Astuti (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The goal of this study is to see how the project method affects early childhood environmental behavior. The children of Kindergarten Group B at PAUD Pandan Wangi Secang, Magelang, are the subjects of this study. This study was carried out because there are issues with children's environmental behavior in terms of waste, plant concern, and water and energy conservation. The project method will help to enhance this low degree of environmental stewardship. This study was designed using an Experimental Research model of Pre-experimental design in the form of One Group Pretest-Posttest Design, which included a pretest, treatment, and posttest. The study was carried out in three stages: planning, implementation, and assessment. The children in this study were from the TK Group B, with a total of 30 youngsters. Observation and interviews are used to acquire data. A parametric test was employed to analyze the data. Through the project technique, the results revealed an increase in children's environmental care behavior. The comparison of the pretest results shows that the lowest score was 15, the highest was 23, and the average was 19. In the meantime, the posttest revealed that the lowest score was 34, the highest was 43, and the average was 38.9. Based on these results, it can be inferred that the project technique has an impact on children in the Kindergarten Group B at PAUD Pandan Wangi Secang Magelang's environmental care behavior.